2021
DOI: 10.1055/s-0041-1728683
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 Related Epilepsies: A Gene Review

Abstract: PRRT2 encodes for proline-rich transmembrane protein 2 involved in synaptic vesicle fusion and presynaptic neurotransmitter release. Mutations in human PRRT2 have been related to paroxysmal kinesigenic dyskinesia (PKD), infantile convulsions with choreoathetosis, benign familial infantile epilepsies, and hemiplegic migraine. PRRT2 mutations cause neuronal hyperexcitability, which could be related to basal ganglia or cortical circuits dysfunction, leading to paroxysmal disorders. PRRT2 is expressed in the cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 155 publications
(258 reference statements)
0
5
0
Order By: Relevance
“…Functional studies demonstrate that these variants result in a reduction in the membrane localization of the PRRT2 protein and impaired interaction with SNAP25. 2,15,16 SCN1A-related conditions constitute a phenotypic spectrum that includes genetic epilepsy with febrile seizures plus (GEFS þ ), hemiplegic migraine, autism spectrum disorder, and developmental and epileptic encephalopathies. 17 Most of the variants show an autosomal dominant pattern of inheritance in which de novo and loss-of-function variants are the most frequently reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Functional studies demonstrate that these variants result in a reduction in the membrane localization of the PRRT2 protein and impaired interaction with SNAP25. 2,15,16 SCN1A-related conditions constitute a phenotypic spectrum that includes genetic epilepsy with febrile seizures plus (GEFS þ ), hemiplegic migraine, autism spectrum disorder, and developmental and epileptic encephalopathies. 17 Most of the variants show an autosomal dominant pattern of inheritance in which de novo and loss-of-function variants are the most frequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies demonstrate that these variants result in a reduction in the membrane localization of the PRRT2 protein and impaired interaction with SNAP25. 2 15 16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BFIE is a familial epileptic syndrome, characterized with focal seizures that may evolve to secondary generalized tonic-clonic seizures. PRRT2 gene, encoding the proline-rich transmembrane protein 2, is a major causative gene for BFIE ( Massimino et al, 2023 ). Gu et al reported seven cases of BFIE effectively managed with anti-seizure medication, all stemming from pathogenic PRRT2 variants.…”
mentioning
confidence: 99%